Do it yourself marketing research / George Edward Breen - Breen, George Edward (1977)
What is do-it yourself marketing research?, evaluation of a problem, how to plan a study, how to use secondary sources, how to conduct a mail questionanire study, how to interview, group interviewing, special research for retallers, what you need to know about sampling, how to write a report that will get action, how to choose an outside research firm, if necessary, company politics how to get your research taken.